La escuela activa como elemento para mejorar la calidad educativa en los niños y niñas de quinto grado de educación general básica de la escuela fiscal mixta Agustín Palacios del barrio San Cayetano Alto, cantón y provincia de Loja, periodo lectivo 2014 – 2015 - Cabrera Quizhpe, Romel Leonel (2015)
The research called "The active school as an element to improve educational quality in children of fifth grade of basic education of the Fiscal Primary School," Agustin Palacios ", aimed to: Understand the theoretical basis of the active schools; diagnose the difficulties encountered in the traditional school and develop a proposal in workshops for teachers; to meet the objectives the quasi-experimental design was used; a methodology comprised scientific, inductive, deductive, analytical and synthetic methods applied; also the technique of the survey, whose results showed that 44% of children never receive help for homework, 44% of them believe that the classes are boring was used; and 100% of teachers believe that poor educational quality is due to the lack of training for them. Since the new education is an opposition to traditional education. On this basis it was concluded that the teachers do not theoretically based active school as an element to improve educational quality, since the lack of teacher training prevents develop the educational quality of the school and the teaching enforces a proposal for workshops training. Corresponding to this we recommend: theoretically substantiate the importance of developing active school; teachers to perform diagnostics on problems that affect the school and the authorities review the proposal and consider its application in the teaching of the institution.